Analysis of Third-Grade Students' Learning Difficulties with Whole Number Operations Based on the Newman Method at SD Negeri 1 Ternate City - Solehatun; Darmawat Hadi; Dwi Widyastuti Nurharyanto (Journal of Creative Power and Ambition (JCPA), 2026)
The purpose of this research is to describe students' learning difficulties in solving problems on natural number material based on the Newman method. The type of this research is descriptive qualitative with data collection techniques including written tests, interviews, and documentation. The subjects in this study are 34 third-grade students from SD Negeri 1 Kota Ternate for the 2025/2026 academic year. Data analysis was conducted thru the stages of data collection, data reduction, data presentation, and conclusion drawing. The research results show that the percentage of errors made by students in solving story problems includes: encoding errors at 44.31%, comprehension errors at 28.80%, transformation errors at 12.41%, process skill errors at 10.93%, and reading errors at 3.55%. Thus, it can be concluded that the most dominant learning difficulty faced by students lies in the final answer writing stage (encoding error), where students tend to directly write down the calculated numbers without systematically including a concluding sentence